Proyecto de factibilidad para la implementación de un restaurante-asadero de pollos en el cantón Sozoranga, provincia de Loja. - MANCHAY CASTILLO, SANTOS ANTONIO (2012)
This research was conducted in the Canton Sozoranga Loja province, aimed at presenting a business proposal entitled: "PROJECT FEASIBILITY FOR THE IMPLEMENTATION OF A RESTAURANT IN Weenie Roast Sozoranga CANTON, ROVINCE LOJA". The same that is oriented to the improvement and development of the economic and social well above Canton, in the province and the country. To make the performance of the different objectives was based on knowledge and theoretical framework to present an appropriate proposal, he also need to use research materials and methods as are, inductive and deductive techniques were also used to gather information such as: the survey, sampling was applied to the Canton Sozoranga PEA and the interview that was applied to the bidders in the same canton. With respect to the Literature Review is the conceptualization of the issues of greatest enhancement that helped develop the research work, they are related to the history of the themed restaurants and on the development of investment projects. In the market study found that there is unmet demand for 25995 units of poultry per year, the same as the Canton citizens are willing to take. Thanks to the technical study found that the installed capacity will be 43,800 units and our capacity utilization would be 10,905 chickens a year and the location of the company will be in Canton Sozoranga. The study organizational levels established legislative, executive, consultant, assistant support, and operational and determined the functions of each job in the manual functions. The name of the company is OUR LADY OF CARMEN Cia. Ltd. Within the financial study determined that the initial investment is $ 15,313.60; project financing would be through equity totaling $ 10,313.60 external capital and the remaining amount is 5000.00 dollars, the price to be offered a roast chicken for the first year is $ 11. With the financial evaluation could determine the project feasibility level, the cost / benefit ratio indicates that for every dollar invested 1.00 get $ 0.47 profit. The results obtained throughout the investigation, we can confirm the problem, ie the technical, economic and financial implement Weenie Roast Restaurant in Canton Sozoranga as it will help the economic and social development of the Canton, Province and Country